Impact of sociocultural factors in the reproductive health of women in Guayaquil University - Roberto André Calderón León; Marlene Elizabeth Sánchez Mata (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: The sexual and reproductive health is important for the general well-being of women and decisions making on the family planning; however, there are sociocultural factors that condition unfavorably the abovementioned aspects.  Objective: To determine the sociocultural factors that conditioned unfavorably the reproductive health of students atGuayaquilUniversity. Methods: A descriptive and observational investigation of 120 students was carried out, they attended the gynecoobstetrics service ofGuayaquil University,Ecuador, during 2019. Results: The interviewed aged 18 and 29 (82.0 %); 55 % didn't receive or ignored the existence of sexual orientation services that were offered to the adolescents of this university. Also, 60.0 % of women stopped going to health centers to get ready on topics of sexual and reproductive health and they abandoned the protection when having sexual relationships due to lack of economic means. Conclusions: The sociocultural factors influenced significantly in the access to the services of sexual and reproductive health that were offered to the adolescents in the university with emphasis in the absence of economic means.